ANALISIS PENENTUAN HARGA POKOK PRODUKSI IKAN ARWANA (Studi Kasus Pada Peternak Di Kabupaten Kapuas Hulu) - Febriati; Jarop, Victorius; Fakhrul Yahya, Rizki; Sartono (Program Studi Akuntansi Universitas Panca Bhakti, 2022)
This study focuses on the discussion of the calculation of the cost of production of arowana fish by arowana fish farmers in Putussibau Selatan District, Kapuas Hulu Regency and uses the Full Costing method. This study uses a qualitative descriptive method, namely describing, explaining, or summarizing various phenomena or various research variables according to events as they are. Data collection techniques in this study using interview techniques, direct observation to the field and using the literature that supports the object under study. Based on the data analysis of the calculation of the cost of production carried out by arowana fish cultivators, in the calculation of the cost of production carried out there are several elements of production costs that are not calculated and are not in accordance with accounting science, arowana fish cultivators as a whole calculate the costs incurred without any grouping or the allocation of production costs from raw material costs, direct labor costs and factory overhead costs. cost calculations carried out by arowana fish cultivators without taking into account maintenance costs, depreciation costs and post-harvest costs. The calculation uses the Full Costing method, which takes into account all elements of production costs and can fairly describe the costs incurred by arowana fish farmers in their production activities.